PURCHASE COMPUTER SYSTEM OF PAYMENT BY CREDIT ON PT. JADIN PRATAMA - Oky Harayanto; Irfan Irfan SKom, MMSI (Jurnal Sistem Informasi, 2002)
PT. JADIN PRATAMA is a company which is engaged in computer sales with credit. The company has a weakness in the storage of employee data, especially in the credit payment system which still use manual recording, common errors and more data is lost or stuck, so that such data is very detrimental to the company. Basically every company expects the existence of a data processing the true and accurate to solve problems in data processing and to support decision-making on the part of corporate leadership. Therefore in this paper, the author tries to computerized data processing, accounts receivable process by using tools to develop the system. The tools that are used for design and develop accounts receivable system including context diagrams, DFD, ERD, FOD proposed and Normalization.